Gender and Age Differences in Consumer Materialism - Ondrijová, Ivana (Technium Business and Management, 2024)
This study explores the relationship between consumer materialism and demographic factors, focusing on gender and age. Materialism, often characterized by the prioritization of acquiring material goods, has been linked to diminished well-being and psychological challenges. The research utilized a sample of 137 respondents surveyed via an online questionnaire measuring materialistic tendencies using Richins’ and Dawson’s (1992) methodology. The findings revealed no statistically significant correlation between materialism levels and gender, aligning with some prior research while contradicting studies suggesting gender-based differences in materialistic values. In contrast, the results confirmed significant age-related differences: respondents under 30 exhibited higher materialism scores compared to older participants. These results reflect trends identified in previous studies linking youth materialism to social comparisons and aspirational behaviors amplified by social media and peer influence. The study contributes to the broader understanding of consumer materialism by highlighting the nuanced impact of demographic factors. However, it also acknowledges limitations, including the use of a non-representative sample and self-reported data. Future research should explore these dynamics further, particularly in diverse cultural and socio-economic contexts.